FoCupin1, a Cupin_1 domain-containing protein, is necessary for the virulence of Fusarium oxysporum f. sp. cubense tropical race 4 - Yan, Tiantian; Zhou, Xiaofan; Li, Jieling; Li, Guanjun; Zhao, Yali; Wang, Haojie; Li, Huaping; Nie, Yanfang; Li, Yunfeng (Frontiers in Microbiology, 2022)
Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is an important soilborne fungal pathogen that causes the most devastating banana disease. Effectors secreted by microbes contribute to pathogen virulence on host plants in plant-microbe interactions. However, functions of Foc TR4 effectors remain largely unexplored. In this study, we characterized a novel cupin_1 domain-containing protein (FoCupin1) from Foc TR4. Sequence analysis indicated that the homologous proteins of FoCupin1 in phytopathogenic fungi were evolutionarily conserved. Furthermore, FoCupin1 could suppress BAX-mediated cell death and significantly down-regulate the expression of defense-related genes in tobacco by using the Agrobacterium-mediated transient expression system. FoCupin1 was highly induced in the early stage of Foc TR4 infection. The deletion of FoCupin1 gene did not affect Foc TR4 growth and conidiation. However, FoCupin1 deletion significantly reduced Foc TR4 virulence on banana plants, which was further confirmed by biomass assay. The expression of the defense-related genes in banana was significantly induced after inoculation with FoCupin1 mutants. These results collectively indicate FoCupin1 is a putative effector protein that plays an essential role in Foc TR4 pathogenicity. These findings suggest a novel role for cupin_1 domain-containing proteins and deepen our understanding of effector-mediated Foc TR4 pathogenesis.